A selective and sensitive fluorescent sensor for cysteine detection based on bi‐8‐carboxamidoquinoline derivative and Cu2+ complex. (20th September 2017) - Chai, Guoping; Liu, Qingwen; Fei, Qiang; Zhang, Jinling; Sun, Xiaoxiao; Shan, Hongyan; Feng, Guodong; Huan, Yanfu
Abstract: In this paper, a novel fluorescent sensor1 for selective and sensitive detection of cysteine was developed based on a complex between bi‐8‐carboxamidoquinoline derivative ligand (L ) and Cu 2+ . The interaction of Cu 2+ with the ligand causes a dramatic fluorescence quenching most likely due to its high affinity towards Cu 2+ and a ligand–metal charge transfer (LMCT) process. The in situ generatedL–Cu 2 complex was utilized as a chemosensing ensemble for cysteine. In the presence of cysteine, the fluorophore, L, was released fromL–Cu 2 complex because of the strong affinity of cysteine to Cu 2+ via the Cu–S bond, leading to the fluorescence recovery of the ligand. The proposed displacement mechanism was confirmed by the results of mass spectrometry (MS) study. Under optimized conditions, the recovered fluorescence intensity is linear with cysteine concentrations in the range 1 × 10 −6  mol/l to 8 × 10 −6  mol/l. The detection limit for cysteine is 1.92 × 10 −7  mol/l. Furthermore, the established method showed a highly sensitive and selective response to cysteine among the 20 fundamental α‐amino acids used as the building blocks of proteins, after Ni 2+ was used as a masking agent to eliminate the interference of His. The proposed sensor is applicable in monitoring cysteine in practical samples with good recovery rate.